New flexible endoscopic full-thickness suturing device: a triple-arm-bar suturing system - Mori, H.; Kobara, H.; Rafiq, K.; Nishiyama, N.; Fujihara, S.; Kobayashi, M.; Oryu, M.; Fujiwara, M.; Suzuki, Y.; Masaki, T. (Endoscopy, 2013)
Background and study aim: A reliable full-thickness suturing device is necessary for pure natural orifice transluminal endoscopic surgery (NOTES). The present study focused on assessing the reliability of a new suturing device. Methods: A total of 60 single sutures were tested to close 5-cm incisions in 8-cm square pieces of resected swine stomach. Each incision was sutured by an over-the-scope clip (OTSC; n = 20), a single hand-sewn stitch (n = 20), or a single triple-arm-bar suturing system (TBSS) stitch. The maximum pulling force durability (MPD) of each suture was tested. To assess the reliability of the TBSS for endoscopic full-thickness resection (EFTR), 60 EFTRs of 50 mm diameter were performed on excised swine stomachs. After EFTR, full-thickness sutures were made using 3-stitch OTSCs (n = 20), 10-stitch hand-sewn sutures (n = 20), or 10-stitch TBSS sutures (n = 20). Outcomes were the MPD test for both single stitch and multiple stitch applications and the suturing time for single-stitch sutures.Results: In the single-stitch MPD tests, there were significant differences between OTSCs and hand-sewn sutures (P = 0.0002) and between OTSCs and TBSS sutures (P = 0.0001), but no significant difference between hand-sewn and TBSS sutures. The multiple-stitch sutures revealed significant differences between OTSCs and hand-sewn sutures (P = 0.0039), and between OTSCs and TBSS sutures (P = 0.013). There was no significant difference between hand-sewn and TBSS sutures. There were significant differences in suture times between OTSC, hand-sewn sutures, and TBSS sutures (P < 0.05). Conclusions: Both single-stitch and multiple-stitch sutures using TBSS have similar strength to hand-sewn sutures. TBSS is a reliable suturing device.